Analysis Financial Management Behavior through Financial Literacy: Gen Z's Preferences Fintech, FoMO, Love of Money - Hari Wahyuni; Eni Erwantiningsih; Agnes Ratna Pudyaningsih (Jurnal Manajemen dan Kewirausahaan, 2025)
In the digital era, Gen Z's financial behavior is shaped by technology and emotions. Financial literacy plays a key role in filtering emotional influences and guiding Gen Z toward smarter financial decisions. This study explores how Gen Z in Pasuruan City uses financial technology (abbreviated as fintech), and how their fear of missing out (FoMO) and attitudes toward money influence their financial habits—particularly through the lens of financial literacy. Using purposive sampling, the research finds that fintech offers real benefits for Gen Z, especially in terms of convenience, security, and privacy. These features make it easier for them to manage money, though a solid understanding of financial literacy remains essential for shaping responsible financial behavior. Interestingly, FoMO—though emotionally strong—does not significantly affect how they manage finances when filtered through financial literacy. Emotional and social factors, like self-control and support from others, seem to matter more. On the other hand, a strong desire for money, even when paired with good financial knowledge, tends to reduce healthy financial behavior. This suggests that emotional ties to money can overpower financial understanding. In short, while fintech helps Gen Z take control of their finances, emotional factors like FoMO and love of money need to be addressed more deeply to truly support smart financial decision-making.